Effect of water absorption on the mechanical properties of n-SiC filled recycled cellulose fibre reinforced epoxy eco-nanocomposites - Alamri, Hatem; Low, It Meng (Elsevier Ltd, 2012)
The effect of the addition of n-SiC particles on water absorption of n-SiC reinforced RCF/epoxy eco-nanocomposites was studied. Results indicated that water uptake decreased as n-SiC content increased. This was also shown by FTIR observation. The effect of water absorption on the mechanical properties of n-SiC filled RCF/epoxy eco-nanocomposites was investigated as a function of n-SiC content. Due to water absorption, flexural strength, flexural modulus and fracture toughness of n-SiC filled RCF/epoxy eco-nanocomposites significantly decreased compared to dry composites. The effect of n-SiC on these mechanical properties was found to be positive. Flexural strength, flexural modulus and fracture toughness increased by 14.4, 7.5 and 6.1%, respectively, compared to unfilled RCF/epoxy composites after the addition of 5 wt% n-SiC. SEM results showed clean pull out of cellulose fibres as a result of degradation in fibre-matrix interfacial bonding by water absorption. The addition of n-SiC was found to enhance the interfacial adhesion between fibre and matrix.